Concomitant Use of Fourier Transform Infrared Attenuated Total Reflectance Spectroscopy and Chemometrics for Quantification of Multiple Adulterants in Roasted and Ground Coffee - Nádia Reis; Adriana S. Franca; Leandro S. Oliveira (Journal of Spectroscopy)
This paper proposed the joint use of Fourier Transform Infrared Attenuated Total Reflectance Spectroscopy (FTIR-ATR) and Partial Least Square (PLS) regression for the simultaneous quantification of four adulterants (coffee husks, spent coffee grounds, barley, and corn) in roasted and ground coffee. Roasted coffee samples were intentionally blended with the adulterants, at adulteration levels ranging from 0.5 to 66% w/w. A robust methodology was implemented in which the identification of outliers was carried out. High correlation coefficients (0.99 for both calibration and validation) coupled with low degrees of error (0.69% for calibration; 2.00% for validation) confirmed that FTIR-ATR can be a valuable analytical tool for quantification of adulteration in roasted and ground coffee. This method is simple, fast, and reliable for the proposed purpose.